2014
DOI: 10.1159/000358676
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Protects Against Senescence and Apoptosis via the RAS-Mitochondria in High-Glucose-Induced Endothelial Cells

Abstract: Backgrounds: Autophagy is an important process in the pathogenesis of diabetes and plays a critical role in maintaining cellular homeostasis. However, the autophagic response and its mechanism in diabetic vascular endothelium remain unclear. Methods and Results: We studied high-glucose-induced renin-angiotensin system (RAS)-mitochondrial damage and its effect on endothelial cells. With regard to therapeutics, we investigated the beneficial effect of angiotensin-converting enzyme inhibitors (ACEIs) or angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 40 publications
(65 reference statements)
3
55
0
1
Order By: Relevance
“…The vascular endothelium is a critical player in the pathogenesis and progression of coronary artery disease [1], hypertension [2], diabetic cardiomyopathy [3], stroke and heart failure [4]. Vascular remodeling is a process responsible for the complex, dynamic interactions between different cell types, including endothelial cells, mesenchymal smooth muscle-type cells and fibroblast cells [5, 6], of which changes of endothelial cell are necessary and essential for the remodeling process.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular endothelium is a critical player in the pathogenesis and progression of coronary artery disease [1], hypertension [2], diabetic cardiomyopathy [3], stroke and heart failure [4]. Vascular remodeling is a process responsible for the complex, dynamic interactions between different cell types, including endothelial cells, mesenchymal smooth muscle-type cells and fibroblast cells [5, 6], of which changes of endothelial cell are necessary and essential for the remodeling process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that increased oxidative injury in diabetic hearts may trigger the activation of stress signalling pathways, facilitating cardiomyocyte cell death [26,27]. However, recent evidence also suggests that, in addition to apoptosis, other processes, such as autophagy, may also be involved in controlling cell death in the pathogenesis of diabetic cardiomyopathy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy flux is increased in the endothelial cells after high-glucose or nutrient deprivation and aortic endothelium of diabetic rat model [5,6]. An experimental approach to reproduce nutrient deprivation consists of the removal of growth factors or serum deprivation [7,8].…”
Section: Introductionmentioning
confidence: 99%